THE IMPORTANCE OF INNOVATIONS FOR THE DEVELOPMENT OF FRANCHISING SYSTEMS - Stanković, Milica S (International Journal of Economic Practice and Policy, 2014)
In today's global competitive business environment, innovations are crucial for the success of the company. It is necessary to emphasize the importance of understanding wishes and needs of consumers and an innovative manner in which their needs can be met more efficiently in comparison to competition. Franchising is, certainly, one of the business concepts that is difficult to associate with innovation, as it presents the use of a proven business model. At the global level, there is a constant tendency in the development of existing and new franchise systems. In this regard, the paper points out the importance of innovation for the development and improvement of the franchise systems. The phenomenon of open innovation is increasingly important in recent years. The paper highlights the importance of open innovation as the best way to innovate the franchising company's business through the adoption of ideas from the external environment and the exchange of internally created ideas. The model of open innovation involves the integration of customers, suppliers and franchisees in the new product development process. The open strategy of new product development is very important for franchising companies that want to be leaders. The paper reviews the development perspectives of open innovation in franchising systems in the future.
Keywords: FRANCHISING; INNOVATIONS; franchisees; new product development; open innovation; customers; strategic imperatives; innovative concept